Cyclic behavior of single shear steel-to-steel screws and powder-actuated fastener connections. (1st October 2021) - Boadi-Danquah, Eugene; Yount, Tristan; Collins, William; Fadden, Matthew
Highlights: Cyclic behavior of screw and powder-actuated fasteners in light-gage steel is tested and characterized. Parameters of fastener behavior are developed to accurately characterize hysteretic joint behavior in analytical models. Thickness limits currently used in specifications can be increased to include additional steel gages. Abstract: An experimental program was undertaken to assess the cyclic performance of screw and powder-actuated fastener connections in light-gage steel to understand their suitability for use in seismic design and other low-cycle fatigue applications. In addition to evaluating commonly used but previously untested steel gages, this study represents a contribution to the field by characterizing the cyclic behavior of powder-actuated fasteners, data which does not currently exist in the literature. Combinations of different fasteners and steel components created nine distinct joints. These joints were composed of steel ranging from 16-gage to 12-gage, with single-lap connections made with No. 10 and No. 12 screws, as well as powder-actuated fasteners, were examined, with goals of comparing peak loads with code formulations and characterizing the hysteretic behavior. Each joint type was subjected to a monotonic displacement protocol, and the load-deformation responses were used to determine an appropriate unified displacement protocol for cyclic testing. The screw joints were then subjected to quasi-static, 0.5 Hz, and 3 Hz cyclic displacement protocols, while the PAF joints were only subjected to the quasi-static cyclic displacement protocol. The peak loads recorded from the tests generally have a close agreement to strength values from code formulations. Typically, increasing the loading rate increased the peak loads recorded. Additionally, from the quasi-static results of the experimental program, finite element modeling parameters for characterizing the cyclic load-deformation backbone, and unloading-reloading response have been derived for the joint configurations.